2009
DOI: 10.1002/pssc.200982547
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and p‐type conductivity control of AlGaN for high‐efficiency nitride‐based UV emitters

Abstract: Microstructural analysis was carried out to clarify the compositional dependence of the generation of dislocations in AlxGa1‐xN on an underlying AlN layer grown by metalorganic vapor phase epitaxy. When the film thickness is less than 1.5 μm, the threading dislocation density (TDD) increases with decreasing AlN molar fraction. However, when the film thickness exceeds 1.5 μm, TDD becomes maximum at x around 0.5. The growth of AlGaN on a grooved AlN template is effective in reducing TDD for all AlN molar fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Whereas the defect structure of pseudomorphic layers with a high Al content does not change significantly compared to the AlN underneath, strain relaxation through formation of additional threading dislocations is observed with decreasing Al content [22]. In the following, to visualize the defect distribution in Al x Ga 1 À x N layers grown on low dislocation density ELO-AlN templates, we have chosen Al x Ga 1 À x N with Al content x of 0.8 and 0.5 as two examples.…”
Section: Defect Distribution In Al X Ga 1 à X N Layers On Elo-aln(m)mentioning
confidence: 82%
“…Whereas the defect structure of pseudomorphic layers with a high Al content does not change significantly compared to the AlN underneath, strain relaxation through formation of additional threading dislocations is observed with decreasing Al content [22]. In the following, to visualize the defect distribution in Al x Ga 1 À x N layers grown on low dislocation density ELO-AlN templates, we have chosen Al x Ga 1 À x N with Al content x of 0.8 and 0.5 as two examples.…”
Section: Defect Distribution In Al X Ga 1 à X N Layers On Elo-aln(m)mentioning
confidence: 82%
“…Since the depth of Mg acceptors is quite high and causing severe problems in devices sensitive to the series resistance of the p-region, such as LEDs or LDs, changes in the structural quality and electronic properties of GaN:Mg occurring as the Mg concentration increases have been looked into in some detail. It turns out that, for high Mg concentrations approaching 10 2 cm À3 , a high density of inversion boundary domains (IBDs), stacking faults (SFs) and dislocations is generated due, as it is thought, to forming of Mg 2 N 3 precipitates limiting the Mg solubility [97][98][99][100][101]. The high density of IBDs causes the inversion of the dominant growth plane mode from Ga-polar at low Mg concentration to N-polar at high Mg concentration [99], with consequent increase in the uptake of Si and O shallow donors and increased compensation [97][98][99].…”
Section: Mg In Iii-nitridesmentioning
confidence: 99%
“…The Mg level was placed based on these measurements close to E v +(0.15-0.17) eV. There has been some published evidence on the level becoming more shallow with increasing Mg acceptors concentration [97]. The effect has been ascribed, as usual, to the overlap of the individual Mg acceptor wave functions resulting in the formation of an impurity band.…”
Section: Mg In Iii-nitridesmentioning
confidence: 99%
“…The reduction of the threading dislocation (TD) density of AlGaN on AlN was observed when the thickness of AlGaN was increased. At the same time, it was also observed that Al 0.5 Ga 0.5 N on AlN still had the highest TD density, indicating that merely increasing the thickness is not very effective for reducing the TD density of Al 0.5 Ga 0.5 N. A further decrease in TD density can be achieved by using a grooved AlN template [2,3]. However, an additional etching process is necessary, and the growth of Al 0.5 Ga 0.5 N on the grooved AlN template might be complicated.…”
mentioning
confidence: 80%
“…The compositional dependence of the generation of dislocations in Al x Ga 1-x N on underlying AlN has been reported [2]. The reduction of the threading dislocation (TD) density of AlGaN on AlN was observed when the thickness of AlGaN was increased.…”
mentioning
confidence: 95%